Political Competition and Public Procurement Outcomes. (August 2019) - Broms, Rasmus; Dahlström, Carl; Fazekas, Mihály
This article asks if low political competition is associated with more restricted public procurement processes. Using unique Swedish municipal data from 2009 to 2015, it demonstrates that when one party dominates local politics, noncompetitive outcomes from public procurement processes are more common. What is most striking is that the risk of receiving only one bid, on what is intended to be an open and competitive tender, considerably increases with long-standing one-party rule. The article contributes to a significant body of work on the detrimental effects of low political competition, and the results are particularly interesting from a comparative perspective because Sweden—an old democracy with a meritocratic bureaucracy, characterized by low levels of corruption and clientelism—is a highly unlikely case in which to find such tendencies.